Effects of solid foods on growth of bottle-fed infants in first three months of life. Issue 6078 (2nd July 1977) - Davies, D P; Gray, O P; Elwood, P C; Hopkinson, C; Smith, S
Abstract : We studied 821 infants who were bottle-fed from birth to determine whether non-milk solids begun within the first 3 monts of life affect early growth. The infants were seen seven to 10 days and three months after birth. They were divided into three groups-those who had started solids before 6 weeks of age (657 infants); those who had started solids between the ages of 6 weeks and 3 months (124 infants); and those given cow's milk formulae alone during the first three months (40 infants). The infants were weighed and measured seven to 10 days after birth and at three months. Mean weekly rates of weight and length gain over the 3 months were calculated and did not differ significantly between the three groups. As no record was made of quantities of food taken we cannot explain the failure of solid foods to affect growth. Studies of how young infants utilise these foods are needed.